Challenges in Managing Marine Bio-invasions via Shipping in Singapore - Lim Chin Sing; Koh Siang Tan (Universitas Gadjah Mada, 2018)
The economic, social and environmental impacts arising from the transfer and establishment of non indigenous marine species (NIMS) mediated through ship hull biofouling and ballast water discharges in the coastal marine environment require a regional approach to manage bio-invasions. As the coordinating body for maritime shipping affairs and protection of the marine environment, the International Maritime Organization (IMO) has been working with member states to adopt and ratify global conventions aimed at preventing invasive species transfer through shipping. As a major shipping hub and port-of-call in Southeast Asia, Singapore faces multiple challenges in managing marine bio-invasions including managing the transit of high risk vessels to environmentally sensitive areas beyond national borders. In this article, global frameworks for managing bio-invasions and its challenges for marine invasive pest management are discussed.